ADDITIVE MODEL OF FORECASTING OF SCRAP METAL CONSUMPTION AT MELT OF STEEL TAKING INTO ACCOUNT SEASONAL FLUCTUATIONS - V. I. Djachenko; D. I. Soshchenko; M. V. Ignatjev (Литьë и металлургия)
The offered and realized additive model of calculation of specific norm of consumption of scrap metal at arc electric steel-smelting furnaces has allowed to reduce considerably the error at calculation of the planned cost price of production.